Diseño básico de un túnel de viento para experimentación con un aerogenerador de eje vertical tipo darrieus (2019)
This document develops the basic design of a wind tunnel taking into account the working conditions of a Darrieus H vertical axis wind turbine. The purpose of this project is to select the type of wind tunnel most suitable for wind turbine experimentation. Vertical axis. Additionally, the requirements to develop this design to the environmental conditions of Bogotá are presented. In the design stage, the equations that govern these calculations, the theoretical and experimental considerations and the design methodology are presented to find the most specific geometry in the different sections that make up the wind tunnel. For the validation of these technical calculations, a simulation by CFD (Computational Fluid Dynamics) was performed in the ANSYS software and finally the costs associated with the manufacture of the wind tunnel were identified.